Initial-State Temperature of Light Meson Emission Source From Squared Momentum Transfer Spectra in High-Energy Collisions - Wang, Qi; Liu, Fu-Hu; Olimov, Khusniddin K. (Frontiers in Physics, 2021)
The squared momentum transfer spectra of light mesons, $π^0$, $π^+$, $η$, and $ρ^0$, produced in high-energy virtual photon-proton ($γ^{*} p$) $→ {\rm meson + nucleon}$ process in electron-proton ($ep$) collisions measured by the CLAS Collaboration are analyzed by the Monte Carlo calculations, where the transfer undergoes from the incident $γ^*$ to emitted meson or equivalently from the target proton to emitted nucleon. In the calculations, the Erlang distribution from a multi-source thermal model is used to describe the transverse momentum spectra of emitted particles. Our results show that the average transverse momentum ($\langle p_T\rangle$) and the initial-state temperature ($T_i$) increase from lower squared photon virtuality ($Q^2$) and Bjorken variable ($x_B$) to higher one. This renders that the excitation degree of emission source, which is described by $\langle p_T\rangle$ and $T_i$, increases with increasing of $Q^2$ and $x_B$.